2022
DOI: 10.1016/j.lanwpc.2021.100370
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of hand, foot, and mouth disease in China, 2013−2019: a population-based study

Abstract: Background Hand, foot, and mouth disease (HFMD) is an important public health problem. A monovalent EV-A71 vaccine was launched in China in 2016. Previous studies showed that inactivated monovalent EV-A71 vaccines were highly efficient against HFMD associated with EV-A71 but not against HFMD with other etiologies, leading to a hypothesis that the introduction of EV-A71 vaccines might change the pathogen spectrum and epidemiological trend of HFMD. In this study, we described for the first time the changing epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 31 publications
0
28
1
Order By: Relevance
“…Previous studies have shown that EV‐A71 vaccines were effective against EV‐A71‐associated HFMD 35 . After the launch of the EV‐A71 vaccine, the proportion of the HFMD cases infected by EV‐A71 decreased, and the cumulative incidence of EV‐A71 serotype HFMD showed a significant decrease in its geographical distribution 36 . CV‐A6 was the main pathogen from 2016 to 2020, especially in 2020.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown that EV‐A71 vaccines were effective against EV‐A71‐associated HFMD 35 . After the launch of the EV‐A71 vaccine, the proportion of the HFMD cases infected by EV‐A71 decreased, and the cumulative incidence of EV‐A71 serotype HFMD showed a significant decrease in its geographical distribution 36 . CV‐A6 was the main pathogen from 2016 to 2020, especially in 2020.…”
Section: Discussionmentioning
confidence: 97%
“…35 After the launch of the EV-A71 vaccine, the proportion of the HFMD cases infected by EV-A71 decreased, and the cumulative incidence of EV-A71 serotype HFMD showed a significant decrease in its geographical distribution. 36 in 2013 and during 2015-2019 in Beijing. 11 The etiological and phylogenetic analysis of HFMD in southern China showed that the predominant virus was also CV-A6 in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, national surveillance of HFMD cases has revealed that the pathogens causing HFMD are constantly changing. After applying the EV-A71 inactivated vaccine marketed in China in 2016, the number of HFMD caused by EV-A71 has decreased rapidly (Hong et al, 2022), whereas the proportion of CVA16 has gradually increased, and the proportion of other EVs in the pathogen spectrum has increased significantly (Chen et al, 2017;He et al, 2018). This indicates that the monovalent EV-A71 inactivated vaccine can prevent 90% of EV-A71-induced HFMD cases, but provides no cross-protection against infection with CVA16 and other EVs (Li et al, 2014;Li et al, 2016;Takahashi et al, 2016), resulting in the consistently high number of CVA16-related HFMD cases.…”
Section: Introductionmentioning
confidence: 99%
“…The most advanced vaccine approach is based upon inactivated virus, and these vaccines have been licensed in PR China, where EVA71 is responsible for periodic outbreaks of HFMD [11][12][13][14][15]. In PR China, the introduction of two-dose vaccination of children aged 6-59 months in December 2015 resulted in an overall reduction in disease and lower rates of serious or fatal infection [16][17][18].…”
Section: Introductionmentioning
confidence: 99%